Age-related Changes in Bone Marrow Mesenchymal Stromal Cells: A Potential Impact on Osteoporosis and Osteoarthritis Development - Ganguly, Payal; El-Jawhari, Jehan J.; Giannoudis, Peter V.; Burska, Agata N.; Ponchel, Frederique; Jones, Elena A. (Cell transplantation, 2017)
Aging at the cellular level is a complex process resulting from accumulation of various damages leading to functional impairment and a reduced quality of life at the level of the organism. With a rise in the elderly population, the worldwide incidence of osteoporosis (OP) and osteoarthritis (OA) has increased in the past few decades. A decline in the number and “fitness” of mesenchymal stromal cells (MSCs) in the bone marrow (BM) niche has been suggested as one of the factors contributing to bone abnormalities in OP and OA. It is well recognized that MSCs in vitro acquire culture-induced aging features such as gradual telomere shortening, increased numbers of senescent cells, and reduced resistance to oxidative stress as a result of serial population doublings. In contrast, there is only limited evidence that human BM-MSCs “age” similarly in vivo. This review compares the various aspects of in vitro and in vivo MSC aging and suggests how our current knowledge on rejuvenating cultured MSCs could be applied to develop future strategies to target altered bone formation processes in OP and OA.